Efeitos da ventilação não invasiva sobre a modulação autonômica cardíaca no pós-operatório de cirurgia de revascularização do miocárdio - Naves, Katrinne Alves de Souza (2015)
The patient in the postoperative of Coronary Artery Bypass Grafting (post-CABG) has impaired cardiac autonomic function. However, there are no studies assessing the influence of ventilation mode during noninvasive ventilation procedure (NIV) in the autonomic cardiac modulation associated with hemodynamic changes. This study was designed to evaluate the autonomic behavior and correlate it with the hemodynamic changes during the execution of NIV with two models of mechanical ventilators in post-CABG. This is a quantitative, prospective, transversal, randomized and crossover study. Patients were selected on the first day postoperative CABG to perform the procedure NIV with two different ventilators: conventional ventilator and the specific ventilator use of NIV for 30 minutes each. The block randomization was used to determine the technique which started to approach then, by crossover perform sequential technique. The positive expiratory pressure was set at 8 cmH2O, the fraction of inspired oxygen was adjusted to maintain oxygen saturation above 90%, the support pressure or inspiratory final pressure were adjusted to maintain a tidal volume (VT) of 8 mL / kg considering the ideal body weight of the patient. The heart rate variability (HRV), blood pressure, heart rate (HR), respiratory rate and oxygen saturation were evaluated at times 5, 10 and 15 minutes before the start of the procedures; at times 5, 10, 15, 20, 25, 30 minutes during application of NIV and 5, 10 and 15 minutes after the procedure. The VT was recorded only for the use of NIV. HRV was analyzed using the straight-line method in the time and frequency domain. To investigate the normality of the data was used the Shapiro-Wilk test and compare the vital data, VT and HRV indices during NIV was used the Wilcoxon test. For the analysis of correlations used the correlation coefficient by Spearman's Postos. Was considered the 95% level of significance with p <0.05. During the performance of NIV with specific ventilator there was significant increase in the HF index (p = 0.0469) and diastolic blood pressure (p = 0.0108). However, during the application of NIV with conventional ventilator there was an increase in HR (p = 0.0228) and systolic blood pressure (p = 0.0003). There was no significant difference between the HRV indexes recorded before and after the procedure. There was also no significant correlation between hemodynamic variables and indices of HRV. The results demonstrate that NIV with specific ventilator shows a slight tendency to increased vagal activation of patients in the PO CRM. There were no hemodynamic changes associated with autonomous behavior on both machines.